PENGARUH PERSEPSI MENGENAI LINGKUNGAN KERJA AUDITOR DAN PERTIMBANGAN PASAR KERJA TERHADAP PILIHAN KARIR SEBAGAI AUDITOR (Studi Kasus pada Mahasiswa Akuntansi Universitas Muhammadiyah dan Universitas - Septiadi (AKT 16 UMY 030, 2016)
This study aims to determine Influence the Perceptions of Auditor’s Job Environment and Job Market Considerations on Career Selection as an Auditor This study uses the independent variable is the auditor’s job environment and Job Market Consideration. The dependent variable is career selection as an auditor. The samples used were accounting students graduate program at the University of Muhammadiyah Yogyakarta and Universitas Ahmad Dahlan. Samples were taken using purposive sampling and respondent data obtained from 117 respondents questionnaires. Moderation statistical methods using multiple linear regression analysis, the statistical test of hypothesis testing t and statistical test F. These results indicate the auditor's job consideration has no effect on the career selection as an auditor. Meanwhile, job market consideration variable has positive influence on career selection as an auditor. Simultaneously, the auditor’s job environment and job market consideration has a significant influence on the career selection as an auditor. Keywords: auditor’s job environment, job market considerations, the career selection as an auditor.